2008
DOI: 10.1111/j.1567-1364.2007.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic reclassification ofCandida stellatastrains reveals frequent occurrence ofCandida zemplininain wine fermentation

Abstract: Yeasts identified as Candida stellata are frequently associated with overripe and botrytized grapes and can survive in the fermenting must until the completion of vinification. The molecular taxonomic examination of 41 strains deposited in six culture collections or described in the literature as C. stellata revealed that most of those isolated from grapes or wines belonged to Candida zemplinina and related species. This confusion around the taxonomic position of the strains may account for the rather controve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 37 publications
2
57
0
Order By: Relevance
“…C. stellata is found in the fermentation of sweet botrytized wines (in which grapes are affected by Botrytis cinerea) and overripe grapes (Rosini et al, 1982;Sipiczki, 2003) and is considered the main agent responsible for the wine aroma-compounds produced (Soden et al, 2000). Nevertheless, it has been demonstrated that in most cases St. bacillaris (C. zemplinina) and St. bombicola (Candida bombicola) have been incorrectly classified as C. stellata (Sipiczki, 2003(Sipiczki, , 2004Sipiczki et al, 2005;Csoma & Sipiczki, 2008). The aroma-compounds may thus be produced by St. bacillaris and/or St. bombicola.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. stellata is found in the fermentation of sweet botrytized wines (in which grapes are affected by Botrytis cinerea) and overripe grapes (Rosini et al, 1982;Sipiczki, 2003) and is considered the main agent responsible for the wine aroma-compounds produced (Soden et al, 2000). Nevertheless, it has been demonstrated that in most cases St. bacillaris (C. zemplinina) and St. bombicola (Candida bombicola) have been incorrectly classified as C. stellata (Sipiczki, 2003(Sipiczki, , 2004Sipiczki et al, 2005;Csoma & Sipiczki, 2008). The aroma-compounds may thus be produced by St. bacillaris and/or St. bombicola.…”
Section: Discussionmentioning
confidence: 99%
“…St. bombicola is also found in honey of Bombus species (bumble-bee) and its osmotolerance seems to be related to the association of this yeast with nectar-feeding insects (Rosa & Lachance, 1998). Similarly, St. bacillaris PYCC6282 is found in Drosophila melanogaster that may play a key role as a vector, transporting the yeast cells from the winery to the ripening grapes in the vineyard (Csoma & Sipiczki, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The C. stellata DBVPG 6714 strain was used for reference. All our isolates showed the same digestion pattern, identical to that described for C. zemplinina (Csoma & Sipiczki, 2008). Sequencing and analysis of the D1/D2 domain of the 26S rDNA was done at the DBVPG.…”
Section: Molecular Characterisationmentioning
confidence: 99%
“…These have a commercial interest, since glycerol ameliorates taste, while low ethanol levels can attract a wide range of consumers. Among Candida species, C. zemplinina occurs most frequently in musts (Csoma & Sipiczki, 2008). Compared to C. stellata, C. zemplinina yeasts have been suggested to be better suited for mixed fermentations, since they could reduce the osmotic stress imposed on Saccharomyces cells more efficiently by removing more sugar from the culture medium (Cavagna et al, 2008;Rantsiou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Lachance et al, 2001a;Nakase et al, 2010;Rosa et al, 2003Rosa et al, , 2007, their strains also occur in wine-related environments and substrates with high sugar concentration. For example, S. bombicola is quite common in fermenting grape must (Csoma and Sipiczki, 2008;Sipiczki et al, 2005) where its presence can favorably affect wine quality (Milanovic et al, 2012). C. kuoi was isolated from concentrated grape juice (Kurtzman, 2012).…”
Section: Resultsmentioning
confidence: 99%